HUBUNGAN POTENSI BAHAYA KERJA PERAWAT DENGAN UPAYA PENCEGAHAN BERBASIS HAZARD IDENTIFICATION RISK ASSESSMENT DETERMINING CONTROL - Lahardi, Rana Purnama; Levyda, Levyda; Kholil, Kholil (LPPMK STIKES Widyagama Husada, 2024)
The quality of health services needs to be maintained and improved, while the number of work accidents still has the potential to occur through the phenomenon of potential work hazards for nurses and low prevention efforts. Information found potential work hazards for nurses include physical, biological, ergonomic, chemical and psychosocial hazards as well as the low prevention efforts of nurses in the Dialysis Room. This study aims to determine the relationship between the potential work hazards of nurses and prevention efforts based on hazard identification risk assessment determining control (HIRADC) in the Dialysis Room at Jasa Kartini Hospital, Tasikmalaya (RSJKT). This research method is a quantitative research type descriptive correlation cross sectional approach. The number of samples was 30 nurses in the Dialysis Room at Jasa Kartini Tasikmalaya Hospital with the sampling technique using total sampling. The instrument used was a valid and reliable questionnaire including a questionnaire on the potential hazards of work for nurses (Cronbach Alpha value 0.953) and HIRADC-based prevention efforts (Cronbach Alpha value 0.952). Data analysis used the Chi-Square test. The results showed that most of the potential work hazards for nurses were in the unsafe category (63.3%). Most of the HIRADC-based prevention efforts are in the low category of 56.7%. There is a significant relationship (p-value = 0.000) between potential work hazards for nurses and HIRADC-based prevention efforts. The results of this study are expected that hospitals hold workshops and training on HIRADC-based prevention efforts regularly at least once a year, nurses improve the patient safety culture implementation program in an effort to minimize potential occupational hazards and further research can explore potential work hazards for nurses and HIRADC-based prevention efforts with the method qualitative research and identify other factors related to HIRADC-based prevention efforts.